Analisis Objektif Dan Mimetik Pada Cerpen “Pelajaran Mengarang” Karya Seno Gumira Ajidarma - Shafaa Rizki Awalliyah Hanafi; Novia Dea Puspita (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
In the literary world, literature is divided into serious literature and popular literature. Serious literature has weightier and more complex writing while popular literature tends to be light and easily understood. Storks belong in popular literature, where they contain lighter stories, and easier words to understand, so that they can be read in different circles. The short stories have intrinsic and extrinsic elements in them. To learn what values the storytellers contain, an objective and mimetic approach is employed to help the reader understand what the writer is trying to say. In the "Pelajaran Mengarang" short, there's a lot of social value that comes from extrinsic. Seno Gumira Ajidarma used several figures of speech that the reader could easily understand. Even values found in intrinsic elements can be understood directly through the lines and conversations found in events. The study was also intended to be beneficial in the development of a brief literary work.